Private Property Deforestation and Regeneration and the Clerk of Forestry in Nineteenth-Century Ontario - Diamantakos, Diamando (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1997)
ABSTRACTBy the latter part of the nineteenth century there was considerable concern in Ontario regarding the loss of forests, as a result of land clearing for agriculture and the harvesting of timber. In response, the provincial government established a department known as the Clerk of Forestry, charged with ensuring a perpetual supply of timber resources and revenues. This department instituted a variety of educational and reforestation initiatives, such as Arbor Day, and the Ontario Tree Planting Act (1883). These initiatives were justified in terms of the supposed effects of forest clearing on the local climate and agricultural productivity. However, their effectiveness was limited by the continuing priority attached to private property rights, doubts concerning the relation between forest loss, climate, and productivity, and a long-standing antagonism towards nature and forests. These issues are examined both in Ontario as a whole, and through a case study of Essex County.